2016
DOI: 10.1021/acs.cgd.5b01775
|View full text |Cite
|
Sign up to set email alerts
|

New Crystallographic Relationships in Biogenic Aragonite: The Crossed-Lamellar Microstructures of Mollusks

Abstract: Crossed-lamellar microstructures are the most common shell-forming biomaterials in mollusks. Because of their complex hierarchical 3D arrangement and small crystallite size, previous crystallographic studies are scarce and have centered on particular species with no comprehensive analysis available. To evaluate the crystallographic diversity of the crossed-lamellar microstructures, we have studied a large set of bivalve and gastropod species with crossed-lamellar layers using X-ray diffraction and electron bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…5(b). Almagro et al 8) concluded that for a/b/2 patterns each 001 maxima and its associated 100 and 010 maxima corresponded Journal of the Ceramic Society of Japan 125 [5] 419-422 2017 exclusively to one of the adjacent 1st-order lamellae, as confirmed by their EBSD analyses. Thus, the a-and b-axes have a 64°r otation with respect to the corresponding ones in the adjacent 1st-order lamellae.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…5(b). Almagro et al 8) concluded that for a/b/2 patterns each 001 maxima and its associated 100 and 010 maxima corresponded Journal of the Ceramic Society of Japan 125 [5] 419-422 2017 exclusively to one of the adjacent 1st-order lamellae, as confirmed by their EBSD analyses. Thus, the a-and b-axes have a 64°r otation with respect to the corresponding ones in the adjacent 1st-order lamellae.…”
mentioning
confidence: 81%
“…Rodriguez-Navarro et al 13) reported that there were two sets of twin laws at the lower (the 3rd-order lamellae) and higher (the 1st-order lamellae) length scales in the crossed-lamellar structure in Conus marmoreus shell. Almagro et al 8) performed XRD and electron backscatter diffraction (EBSD) examinations on the samples of 20 species from Bivalvia and another 20 species from Gastropoda, and identified a detailed crystallographic diversity including nine types of texture patterns, which can be classified into five main groups with significantly different crystallographies. They also pointed out that the crossed-lamellar structure was not a single microstructure but rather a family of homeomorphic microstructures with complex and varied crystallographies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While extensive studies have been focused on the simpler “brick-and-mortar” shell microstructure named nacre1718, there have been limited experimental efforts on the crossed-lamellar structure19 although this type of structure consists of more than 90% species within the Mollusca20. This structure is hierarchically assembled by ordinary brittle inorganic calcium carbonate with only 0.1–1 wt.% organic matrix2122.…”
mentioning
confidence: 99%